The health-related determinants of eating pattern of high school athletes in Goiás, Brazil - Matias Noll; Ana Paula Santos Rodrigues; Erika Aparecida Silveira (BMC, 2020)
Abstract Background Athletes put their health at short- and long-term risk and a detailed investigation of health outcomes is important because it should allow the development of more specific interventions. This study aimed to evaluate the health-related determinants of eating pattern of high school athletes. Methods The study enrolled 248 Brazilian athletes aged 14-20 years. Eating pattern outcomes included skipping breakfast, vegetable and fruit consumption, and sweets consumption. The following factors were considered as independent variables: sociodemographic, economic, anthropometry, body weight control, psychosocial, sedentary behavior, sleeping time, meals, alcohol and smoking, and strength variables. Data were analyzed using Poisson regression model and the effect measure was the prevalence ratio (PR). Results The results showed that 45.6% of the athletes skipped breakfast, 29.8% ate sweets regularly, and only 8.9% consumed vegetables and fruit regularly. Multiple analysis revealed the following positive associations: breakfast skipping and vomiting or using laxatives to lose weight (PR, 1.12; 95% CI, 1.01-1.26); low fruit and vegetable consumption and using pills to lose weight (PR, 1.05; 95% CI, 1.02-1.07); high sweets consumption and female athletes (PR, 1.32; 95% CI, 1.12-1.55); high sweets consumption and more than 2 h spent watching TV (PR, 1.19; 95% CI, 1.02-1.39). Conclusions Our findings indicated that sociodemographic, body weight control and sedentary factors are determinants on eating patterns of high school athletes.